2016
DOI: 10.18632/oncotarget.8019
|View full text |Cite
|
Sign up to set email alerts
|

β-casein nanovehicles for oral delivery of chemotherapeutic drug combinations overcoming P-glycoprotein-mediated multidrug resistance in human gastric cancer cells

Abstract: Multidrug resistance (MDR) is a primary obstacle to curative cancer therapy. We have previously demonstrated that β-casein (β-CN) micelles (β-CM) can serve as nanovehicles for oral delivery and target-activated release of hydrophobic drugs in the stomach. Herein we introduce a novel nanosystem based on β-CM, to orally deliver a synergistic combination of a chemotherapeutic drug (Paclitaxel) and a P-glycoprotein-specific transport inhibitor (Tariquidar) individually encapsulated within β-CM, for overcoming MDR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 58 publications
7
36
0
1
Order By: Relevance
“…The data were analyzed using a nonlinear curve fitting of a sigmoidal model (Hill1) with OriginPro 9.0 for doseresponse curve according to Eq. (3) 59 :…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…The data were analyzed using a nonlinear curve fitting of a sigmoidal model (Hill1) with OriginPro 9.0 for doseresponse curve according to Eq. (3) 59 :…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…Other models oriented on micellar organization deal with dynamic forms [11], including micellar aggregates studied in the context of membrane proteins [12,13]. Studies of micellar forms and their applications in drug transport can be found in [14][15][16][17][18][19]. Notably, the ability to construct a co-micelle (i.e., …”
Section: Introductionmentioning
confidence: 99%
“…Cancer multidrug resistance is the term used to describe a phenomenon in which once a cancer develops resistance to one chemotherapeutic drug, it will become resistant to many (or all) other chemotherapeutic drugs (which may or may not have the same mechanism of action). Cancer multidrug resistance has become a problem that cannot be ignored in clinical practice, and many studies are being carried out to nd ways to combat or reverse it [66][67][68][69][70]. Fu et al reported that the proliferation, migration, and invasion of multidrug-resistant human gastric cancer cell line SGC7901/ADR were signi cantly inhibited by an nhexane extract of ELB in a time-and dose-dependent manner: the cell cycle was arrested in the G2/M phase, and cell apoptosis was induced.…”
Section: Gastric Cancermentioning
confidence: 99%